Pengaruh Dividend Yield, Dividend Payout Ratio (DPR), dan Earning Volatility terhadap Stock Price Volatility Periode 2020-2024 - Safna Kurnia Putri; Romi Adetio Setiawan; Kustin Hartini (Universitas Batanghari Jambi, 2026)
This study aims to determine the simultaneous and partial effects of Dividend Yield, Dividend Payout Ratio, and Earnings Volatility on Stock Price Volatility through panel regression analysis using the Fixed Effects Model (FEM). This study uses a quantitative approach with panel data from companies listed on the Sri Kehati Index on the Indonesia Stock Exchange for the period 2020-2024. The results show that, partially, Dividend Yield and Dividend Payout Ratio have no significant effect on Stock Price Volatility, while Earnings Volatility has a significant effect on Stock Price Volatility. Simultaneously, the variables Dividend Yield, Dividend Payout Ratio, and Earnings Volatility significantly influence Stock Price Volatility in companies listed on the Sri Kehati Index on the Indonesia Stock Exchange for the period 2020-2024.